Pathogenicity of Colletotrichumkahawae in Kenya - Njoka, Fredrick M.; Owaka, Margaret; Omondi, Chrispine; Kathurima, Elijah (My University, 2017)
This study was aimed at determining the virulence diversity of Colletotrichumkahawae, and their correlation with coffee growing regions and interaction with coffee varieties in Kenya. A total of 34 single conidia isolates were obtained and subjected to variation analysis using DNA banding patterns. The test varieties included Rume Sudan, Catimor, K7 and SL 28 (susceptible). Seedlings were individually scored for disease symptoms and mean grade of infection was computed. The mean grade data was then used to perform Analysis of Variance (ANOVA) using the random effects model. The results were used to determine the correlation between molecular polymorphism and diversity in virulence. The variety x isolate interaction effects although significant (p<0.05) did not conclusively reveal the existence of races because the isolate effect was not significant. The virulence tests revealed that variation was due to main effects of varieties. Rume Sudan was highly resistant with a mean grade of 4.75. Catimor with a mean grade of 7.66 showed medium resistance. K-7 showed medium resistance with a mean grade of 9.97. SL 28 was highly susceptible with a mean grade of 11.75. The growing regions had no influence on the genetic and virulence diversity since C. kahawae isolates from all regions were pathogenic on the tested coffee cultivars. All the isolates were significantly (p<0.05) more aggressive on coffee cultivar SL28, followed by K7 and Catimor in that order. Rume Sudan showed high resistance to all the tested isolates irrespective of the region. It is concluded that variation in Colletotrichumkahawae population is largely due to differences in aggressiveness of the isolates.
Keywords: Colletotrichumkahawae; Coffeaarabica; pathogenicity; resistance; races; aggressiveness; polymorphism; isolates